Interdependence of Electricity Markets and Gas: Pending Issues - Navarro, Richard A. (2016)
In this paper, analyzes the problems of interdependence of markets for gas and electricity, through a descriptive and exploratory analysis of academic papers in the last 5 years, where gas dependency highlighted in electricity generation, aspects which they have been discussing separately. This analysis can identify the different lines of research on the interrelationship of both markets, ranging from planning the expansion of the markets for gas and electricity, operation planning of model-based cost optimization markets and analysis of their interactions, all in models where markets interact separately, placing a strong emphasis on identifying missing develop outstanding issues. In the review of restrictions on the interaction of markets, it is observed in all cases, these are analyzed separately, probably by the computational complications of these models. In that sense, it opens a valuable opportunity to develop research in any of the research identified, and for the specific case of a short-term market, the challenge will be to model the inter-temporal derivative of the effect of the combination of a hydro-thermal model.